The Geopolitics of Critical Minerals and the Future of National Economic Sovereignty - Eka Sutisna; Muh. Nur; Muhammad Syukri; Asrul Jabani; Muh. Rezky Naim (Jurnal Pelita Raya, 2026)
Indonesia’s abundance of minerals places the country in a paradoxical position, caught between the opportunity to build new economic sovereignty and the risk of becoming trapped in technological dependence and global economic power imbalances. This study aims to analyse the role of critical minerals in shaping the global economic geopolitical landscape and its implications for efforts to strengthen Indonesia’s national economic sovereignty. The study employs a qualitative approach with an exploratory-analytical economic geopolitical research design. The findings confirm that the future of Indonesia’s economic sovereignty within the geopolitics of critical minerals is not solely determined by the abundance of natural resources, but by the state’s ability to transform mineral wealth into a foundation of technological, institutional, and economic justice capable of critically navigating the complexities of the global green economy, which simultaneously opens up new opportunities for power and the risk of deeper geopolitical inequalities. The practical implications demand a paradigm shift in policy from mere resource nationalism towards a more radical and inclusive strategy of technological and industrial sovereignty, whilst theoretically opening up space for the development of new energy geopolitical studies that are more sensitive to the dimensions of domestic power and global inequality within the green economy.